The Effect of “QuakeGuard” Mobile Application on Resilience among Community Members in Disaster Prone Area in Sukabumi, Indonesia - Budhiana, Johan; Permana, Iwan; Dewi, Rosliana (The Malaysian Journal of Nursing (MJN), 2025)
Background: Traditional disaster preparedness strategies often emphasise structural solutions, but the psychological and social dimensions of resilience have received less attention. Innovative approaches, such as mobile applications like "QuakeGuard," offer promising avenues to address this gap. Objectives: This study aimed to assess the effectiveness of the "QuakeGuard" mobile application in strengthening resilience among community members in disaster-prone areas of Sukabumi, Indonesia. Methods: A quasi-experimental study design with pre-test and post-test measurements was employed, with data collected at three repeated measurements. A total of 320 participants were recruited through convenience sampling and assigned to either the intervention group (n = 160) or the control group (n = 160). Community resilience was assessed using the Conjoint Community Resiliency Assessment Tool (CCRAT). Data analysis was performed using repeated measures ANOVA, Cohen’s d test, and generalised estimating equations (GEE). Results: The intervention group demonstrated significant improvements in community resilience over time compared to the control group (p < 0.05). The post-test resilience scores for the intervention group (Mean ± SD: 2.93 ± 1.54) were significantly higher than those for the control group (Mean ± SD: 2.56 ± 1.06, p = 0.012). GEE analysis showed a significant interaction effect (ß = 5.09, 95% CI: 2.10–8.75, p = 0.001). Conclusion: The "QuakeGuard" mobile application proved to be an effective tool for enhancing community resilience by providing user-friendly and culturally relevant disaster preparedness resources. Further studies should investigate the long-term effects and scalability of such interventions in diverse communities.